Etiopathogenesis, Classical Immunotherapy and Innovative Nanotherapeutics for Inflammatory Neurological Disorders - Jose Sa, Maria; Guimaraes, Joana; Abreu, Pedro; Mendes, Amelia; B. Souto, Eliana (Current Nanoscience, 2011)
Central nervous system (CNS) inflammation and neurological diseases are clinical conditions requiring a multifaceted spectrum of immunotherapies. The present paper reviews the etiopathogeny of demyelinating diseases located in the CNS (e.g., multiple sclerosis, acute disseminated encephalomyelitis, and neuromyelitis optica), and in the peripheral nervous system (e.g., acute/chronic idiophathic inflammatory polyradiculoneuritis, and other dysimmune neuropathies). The pharmacological treatments here discussed include non-specific strategies (e.g., glucocorticoids, intravenous immunoglobulin) and others more specific, such as human IFNβ, glatiramer acetate, mitoxantrone, monoclonal antibodies, fingolimod, laquinimod, cladribine, fumarate, teriflunomide. The immunotherapies are described in terms of their specific and/or multiple activity in the disease stage of development (i.e., initiation, central/peripheral activation, molecular stimulation and immune effector responses during early, transitional and late phases). In the light of the current pharmacological treatments, novel site specific approaches using nanoparticles are briefly addressed.
Keywords: acute inflam-matory demyelinating polyradiculoneuropathy